JEJAK LANGKAH: PERAN TOKOH-TOKOH INSPIRATIF DI KAMPUNG BATIK KAUMAN SURAKARTA - Nurhuda, Deviana; Ayuningtyas, Ardia; Aprilianto, Athanasius Agung Budi; Puspitasari, Diah Ayu; Hapsari, Marchelina Dwi; Wiganingrum, Anditya (Universitas Negeri Malang, 2024)
Abstract: Kauman Batik Village, Surakarta, is not only famous for its beautiful batik cloth, but also has inspiring stories of its characters. This article examines the important role of inspirational figures from various backgrounds in building and advancing this village. Their contribution does not only stop at preserving batik, but also in economic development and promotion of Kauman Batik Village as a tourist destination. This article reveals their inspiring stories, figures who dedicate themselves to preserving Kauman batik culture. From the founder of the batik village, who started a business and instilled the noble values of Kauman batik, to successful batik entrepreneurs, who faced various challenges and contribute to the development of the village. Dedicated batik artists also did not escape discussing how they preserve traditional batik motifs and techniques. More than just a biography, this article offers insight into the spirit of Kauman batik, the noble values contained within it, and how these inspirational figures are role models for the younger generation. Kampung Batik Kauman Surakarta has become a cultural icon that is not only famous for the beauty of its batik cloth, but also for the inspiring stories of its characters. They not only play a role in preserving batik, but also in developing the local economy and promoting Kauman Batik Village as an attractive tourist destination. Starting from the founder of the batik village, who persistently started a business and instilled the noble values of Kauman batik, to the batik entrepreneur who successfully faced various challenges and participated in the progress of the village. Apart from that, dedicated batik artists are also the focus of this article, discussing how they keep traditional batik motifs and techniques sustainable. These inspirational figures are not only examples for the current generation, but also become pillars that support priceless cultural heritage. By telling their stories, it is hoped that this article can provide inspiration and a better understanding of the importance of preserving local culture and appreciating the role of figures in advancing it. Abstrak: Kampung Batik Kauman Surakarta, tak hanya terkenal dengan kain batiknya yang indah, tetapi juga menyimpan kisah inspiratif para tokohnya. Artikel ini yang menghadapi berbagai tantangan dan berkontribusi bagi kemajuan kampung. Seniman batik yang berdedikasi juga tak luput dari pembahasan, bagaimana mereka melestarikan mot mengupas peran penting tokoh-tokoh inspiratif dari berbagai latar belakang dalam membangun dan memajukan kampung ini. Kontribusi mereka tak hanya terhenti pada pelestarian batik, tetapi juga dalam pengembangan ekonomi dan promosi Kampung Batik Kauman sebagai destinasi wisata. Artikel ini menguak kisah-kisah inspiratif mereka, tokoh-tokoh yang mendedikasikan diri untuk menjaga kelestarian budaya batik Kauman.Dari pendiri kampung batik, yang merintis usaha dan menanamkan nilai-nilai luhur batik Kauman, hingga pengusaha batik yang sukses, if dan teknik batik tradisional. Lebih dari sekadar biografi, artikel ini menawarkan wawasan tentang semangat batik Kauman, nilai luhur yang terkandung di dalamnya, dan bagaimana para tokoh inspiratif ini menjadi teladan bagi generasi muda. Kampung Batik Kauman Surakarta telah menjadi ikon budaya yang tak hanya terkenal karena keindahan kain batiknya, tetapi juga karena kisah inspiratif yang dimiliki oleh para tokohnya. Mereka tidak hanya berperan dalam melestarikan batik, tetapi juga dalam mengembangkan ekonomi lokal dan mempromosikan Kampung Batik Kauman sebagai destinasi wisata yang menarik. Mulai dari pendiri kampung batik, yang dengan gigih merintis usaha dan menanamkan nilai-nilai luhur batik Kauman, hingga pengusaha batik yang berhasil menghadapi berbagai tantangan dan turut serta dalam kemajuan kampung. Selain itu, seniman batik yang penuh dedikasi juga menjadi fokus artikel ini, dengan membahas bagaimana mereka menjaga motif dan teknik batik tradisional agar tetap lestari. Para tokoh inspiratif ini tidak hanya menjadi contoh bagi generasi saat ini, tetapi juga menjadi pilar yang mendukung warisan budaya yang tak ternilai harganya. Dengan menceritakan kisah-kisah mereka, diharapkan artikel ini dapat memberikan inspirasi dan pemahaman yang lebih baik tentang pentingnya melestarikan budaya lokal dan menghargai peran para tokoh dalam memajukannya.